2015
DOI: 10.3389/fmicb.2015.00902
|View full text |Cite
|
Sign up to set email alerts
|

Cell aggregation promotes pyoverdine-dependent iron uptake and virulence in Pseudomonas aeruginosa

Abstract: In Pseudomonas aeruginosa the Gac signaling system and the second messenger cyclic diguanylate (c-di-GMP) participate in the control of the switch between planktonic and biofilm lifestyles, by regulating the production of the two exopolysaccharides Pel and Psl. The Gac and c-di-GMP regulatory networks also coordinately promote the production of the pyoverdine siderophore, and the extracellular polysaccharides Pel and Psl have recently been found to mediate c-di-GMP-dependent regulation of pyoverdine genes. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 69 publications
3
40
0
6
Order By: Relevance
“…Although the mechanism of biofilm-mediated regulation of pyoverdine remains unclear, there is a strong correlation between biofilm formation and cell aggregation (Visaggio et al ., 2015; Kang and Kirienko, 2017). This was initially identified and investigated by Imperi and colleagues, who demonstrated that the exopolysaccharides Pel and Psl were essential for planktonic cell aggregation and pyoverdine production (Visaggio et al ., 2015).…”
Section: Biofilm Formation Promotes Siderophore Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of biofilm-mediated regulation of pyoverdine remains unclear, there is a strong correlation between biofilm formation and cell aggregation (Visaggio et al ., 2015; Kang and Kirienko, 2017). This was initially identified and investigated by Imperi and colleagues, who demonstrated that the exopolysaccharides Pel and Psl were essential for planktonic cell aggregation and pyoverdine production (Visaggio et al ., 2015).…”
Section: Biofilm Formation Promotes Siderophore Productionmentioning
confidence: 99%
“…This was initially identified and investigated by Imperi and colleagues, who demonstrated that the exopolysaccharides Pel and Psl were essential for planktonic cell aggregation and pyoverdine production (Visaggio et al ., 2015). Artificially inducing cell aggregation, by adding agar to the media for example, was shown to restore pyoverdine in pel psl double mutants (Visaggio et al ., 2015).…”
Section: Biofilm Formation Promotes Siderophore Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ToxA detection, cell-free culture supernatants were supplemented with 6ϫ SDS-PAGE loading dye (375 mM Tris-HCl [pH 6.8], 9% SDS, 50% glycerol, 0.03% bromophenol blue). The volumes of supernatants (or appropriate dilutions) loaded in SDS-PAGE gels were normalized to bacterial growth according to the following formula: loading volume (microliters) ϭ 10/OD 600 for the corresponding bacterial culture (49). Proteins resolved by SDS-PAGE were electrotransferred to a nitrocellulose filter (Hybond-C Extra; Amersham) and probed for ToxA by using a rabbit polyclonal anti-ToxA antibody (Sigma-Aldrich).…”
mentioning
confidence: 99%
“…Although these biofilms may contain low number of viable cells, from a contamination perspective, this could still be relevant as cells within the biofilm are protected against disinfectants by the biomass of dead cells. In P. aeruginosa cell aggregation, either via growth in a colony or by means of exopolysaccharide (EPS) production, has been shown to trigger the production of the siderophore pyoverdine and other virulence factors (Visaggio et al 2015). In Staphylococcus lugdunensis, the cell wall bound IsdC protein involved in iron transport promoted cell aggregation in iron depleted condition (Missineo et al 2014).…”
Section: Iron Sources and Biofilmmentioning
confidence: 99%